AN OVERVIEW OF TECHNOLOGY TRANSFER AS A REGULATORY ASPECT - PAVITHRA, G. M.; MANORANJITH; NAGALAKSHMI, S. (International Journal of Applied Pharmaceutics, 2021)
Technology Transfer is fundamental and crucial to the drug development process for new drug products. The great decision is based on that factor in which the concept or process is advanced from research and development-oriented scheme to aimed towards the commercialization of the drug. The transfer could also be said to achieve success if the receiving section and the transferee can efficiently use the technology for profit. The achievement relies upon an understanding of the process or the capability to predict exactly the future prospects of a process. The main intention of this review article is to study the Regulatory aspects of technology transfer. This review article is mainly focused on the Consequence of technology transfer, the purpose for technology transfer in industries, barriers concerned with technology transfer, classification regarding technology transfer, facets of technology transfer, and steps among technology transferThis review was carried out by systematic searches of data integrity in relevant ICH, WHO, and US guidelines, published articles, reviews and abstracts in Google scholar, Pubmed, Science direct, Embase, Web of science of articles up to 2020.